2021
DOI: 10.1007/s00592-021-01766-y
|View full text |Cite
|
Sign up to set email alerts
|

TIMP3 involvement and potentiality in the diagnosis, prognosis and treatment of diabetic nephropathy

Abstract: Diabetic kidney disease, one of the most severe complications associated with diabetes, is characterized by albuminuria, glomerulosclerosis and progressive loss of renal function. Loss of TIMP3, an Extracellular matrix-bound protein, is a hallmark of diabetic nephropathy in human and mouse models, suggesting its pivotal role in renal diseases associated to diabetes. There is currently no specific therapy for diabetic nephropathy, and the ability to restore high TIMP3 activity specifically in the kidney may rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Diabetic nephropathy is a key factor in the development of CKD ( Molitch et al, 2003 ), with its defining features being an increase in albuminuria, decline in the glomerular filtration rate (GFR), and loss of podocytes. In a retrospective study, the potential roles of TIMP3 and its related noncoding RNA in the progression of diabetic nephropathy were investigated ( Casagrande et al, 2021 ). An example of the moderation of podocellular damage in diabetic nephrotic disease is the overexpression of non-coding RNA (lincRNA) 4930556M19Rik which downregulates miR-27a-3p and upregulates TIMP3 ( Fan and Zhang, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy is a key factor in the development of CKD ( Molitch et al, 2003 ), with its defining features being an increase in albuminuria, decline in the glomerular filtration rate (GFR), and loss of podocytes. In a retrospective study, the potential roles of TIMP3 and its related noncoding RNA in the progression of diabetic nephropathy were investigated ( Casagrande et al, 2021 ). An example of the moderation of podocellular damage in diabetic nephrotic disease is the overexpression of non-coding RNA (lincRNA) 4930556M19Rik which downregulates miR-27a-3p and upregulates TIMP3 ( Fan and Zhang, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Inflammatory Therapy . Inflammation can greatly aggravate the development of DN, so anti-inflammatory therapy is necessary [ 16 ]. Aldose reductase inhibitors act on the polyol pathway, preventing the conversion of glucose to sorbitol.…”
Section: Advances In Dnmentioning
confidence: 99%
“…Early diabetic nephropathy is mostly manifested by increased excretion rate of microalbumin in the urine, and decreased glomerular filtration rate can be seen in renal function examination with the aggravation of the disease. 2 Those with severe disease may involve dialysis and kidney transplantation, and will have a significantly increased probability of cardiovascular disease along with the decline of renal function, which will seriously endanger life safety. 3 Studies have revealed that there is a correlation between nephropathy and abnormal changes in bone metabolism indicators in the body.…”
Section: Introductionmentioning
confidence: 99%